2021
DOI: 10.3389/fgene.2021.795570
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Structure and East-West Population Admixture in Northwest China Inferred From Genome-Wide Array Genotyping

Abstract: Northwest China is a contacting region for East and West Eurasia and an important center for investigating the migration and admixture history of human populations. However, the comprehensive genetic structure and admixture history of the Altaic speaking populations and Hui group in Northwest China were still not fully characterized due to insufficient sampling and the lack of genome-wide data. Thus, We genotyped genome-wide SNPs for 140 individuals from five Chinese Mongolic, Turkic speaking groups including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…The ancient southern Chinese rice farmers finally have developed into several ancestral populations for different linguistic families in East and Southeast Asia, including Hmong-Mien, Austroasiatic, Tai-Kadai, and Austronesian (Zhao, 2010). Indeed, Recent genetic studies based on genome-wide data from modern (Huang et al, 2018;Ren et al, 2019;He et al, 2020He et al, , 2021aHe et al, ,b, 2022aLu et al, 2020;Bin et al, 2021;Ma et al, 2021;Wang et al, 2022) and ancient populations (Yang et al, 2020;Wang et al, 2021c) have demonstrated complex genetic structure in southern China. Wang et al (2022) have identified the genetic substructure between inland and coastal Tai-Kadai people.…”
Section: Introductionmentioning
confidence: 99%
“…The ancient southern Chinese rice farmers finally have developed into several ancestral populations for different linguistic families in East and Southeast Asia, including Hmong-Mien, Austroasiatic, Tai-Kadai, and Austronesian (Zhao, 2010). Indeed, Recent genetic studies based on genome-wide data from modern (Huang et al, 2018;Ren et al, 2019;He et al, 2020He et al, , 2021aHe et al, ,b, 2022aLu et al, 2020;Bin et al, 2021;Ma et al, 2021;Wang et al, 2022) and ancient populations (Yang et al, 2020;Wang et al, 2021c) have demonstrated complex genetic structure in southern China. Wang et al (2022) have identified the genetic substructure between inland and coastal Tai-Kadai people.…”
Section: Introductionmentioning
confidence: 99%
“…The PCA analyses based on individual-level and population-level, the MDS analyses with F ST and D A genetic distances also confirmed the close genetic relationships between Dongxiang group and other East Asian populations. Previous researches based on various genetic markers also indicated that Dongxiang group had closer genetic distances with Chinese other groups, such as the Xibo and Salar groups [ 16 ], Tibetan ethnic group [ 16 , 33 ], Hui, Bonan and Yugur groups [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the northern part of Sichuan is a well-known high-incidence area for EC in China [ 23 ], and there is a significant difference in the incidence rates between high- and low-prevalence areas [ 24 ]. While population genetic studies in China often focus on minority ethnic groups [ [25] , [26] , [27] , [28] ], there is still a relative lack of research on the influencing factors, genetic background, and origins behind the high prevalence of EC among the Han population in the Sichuan region.…”
Section: Introductionmentioning
confidence: 99%